Pierre Cabanis – entre la science du vivant et la science de l’homme - Loba, Mirosław (Studia Romanica Posnaniensia, 2018)
The main goal of the study is to show the novelty of Cabanis’s project. As a scientist, doctor and philosopher, the author of Rapports du physique et du moral de l’homme attempts to find a new science called anthropology, based mostly on physiology. There is also a discussion of how sensations are transformed (“translated”) into signs and ideas. In his dream of progress of human society, Cabanis has to navigate between the organic conception of the human being and vitalism, which can be seen as a critical approach to any scientific reductionism.